An investigation into influences of L1 on English paragraph writing performance by Vietnamese EFL learners : - Trần, Triều Huyên (Trường Đại học Cần Thơ, 2020)
Research on the challenges that EFL learners usually face in their L2 writing process has indicated that mother tongue (L1-transfer) has influenced second language writing. This research aims to (1) identify common errors made by Vietnamese EFL learners in their written paragraphs, and (2) investigate learners’ perceptions of the causes of such errors as well as L1-transfer errors. In this mixed method study, the quantitative data was firstly collected by employing error analysis to categorize errors in 69 written paragraphs of 69 grade 11 students in an upper secondary school in An Giang province. Then, a semi-structure interview with each of 20 students who made the most errors in paragraph writings was carried out to explore their perception on errors influenced by their first language. The results showed that the participants made both intralingual and interlingual errors as verb-related errors including verb voice and subject-verb agreement were among the most prominent ones in grammatical errors, while calque and collocations errors caused significant problems in the lexis aspect. Regarding the causes of the L1- transfer errors, two main causes have been identified: the difference between Vietnamese and English, and the learner’s habit of using L1. Moreover, the study found that intralingual transfer including overgeneralization or analogy was one of the causes of the errors. The study then presented important pedagogical implications for English language learning and teaching, and was expected to be beneficial to stakeholders in the ESL / EFL context.